Design and Analysis of a Novel Chaos-Based Image Encryption Algorithm via Switch Control Mechanism - Xiao, Shenyong; Deng, YaShuang; Yu, ZhiJun (Security and communication networks, 2020)
Chaos has been widely used in image encryption due to its rich properties. However, it remains an irreconcilable contradiction for security and implementation efficiency for image encryption schemes. In this paper, a novel chaos-based image encryption scheme has been proposed, where the Lorenz chaotic system is applied to generate pseudorandom sequences with good randomness, and a random switch control mechanism is introduced to ensure the security of the encryption scheme. Experimental results demonstrate the effectiveness and superiority of the algorithm.